Trends in Total Hip Arthroplasty in Germany from 2007 to 2016: What Has Changed and Where Are We Now? - Klug, Alexander; Gramlich, Yves; Hoffmann, Reinhard; Pfeil, Joachim; Drees, Philipp; Kutzner, Karl Philipp (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background The number of total hip arthroplasties (THA) is rising in many industrialized nations. At the same time, the evidence regarding different types of prostheses and fixation techniques is constantly evolving. Therefore, this study aimed to analyze changes in THA by these advancements during the last decade.Methods A retrospective analysis of data provided by the Federal Statistical Office of Germany from 2007 to 2016 was conducted using codes from the German procedure classification system and associated International Statistical Classification of Diseases and Related Health Problems codes. THA procedures were evaluated according to diagnoses, sex, and age of patients, along with the distribution of different prosthesis types. Additionally, changes in these parameters over time were analyzed.Results From 2007 to 2016 a total of 2 157 041 primary THA procedures were performed in Germany, with an increase of 14.4% over this period. Overall, cementless standard THA (STHA) was used most frequently (50.0%), followed by hybrid variants (18.8%), hemiarthroplasties (15.9%), cemented standard THA (cSTHA; 9.2%), cementless short-stem THA (ssTHA; 4.8%), and hip resurfacing (HR; 0.9%) techniques. During the study period, the number of cSTHA and HR decreased significantly, whereas the use of STHA and ssTHA rose substantially, with a significantly higher application of these procedures in the elderly population. While osteoarthritis of the hip joint was the main indication for THA, several procedure-specific differences were identified.Conclusion The present data clearly demonstrate an increase in the use of cementless fixation for THA in Germany during the last decade and document a rise in ssTHA in recent years with, in contrast, the use of HR decreasing to a minimum.
Keywords: total hip arthroplasty; trends; short stem; cementless; hip resurfacing